Environmental, social, and governance materiality in XBRL disclosures and its performance predictability: Evidence from Japan - Jiaqi Yang; Kotaro Takahashi; Satoru Yamadera; Shu Tian (Asian Development Bank (ADB), 2024)
By gathering and analyzing the textual information in eXtensible Business Reporting Language format from the annual securities reports of around 3,800 Japanese listed companies from 2013 to 2023, this study aims to uncover the trend of Japanese corporate environmental, social, and governance (ESG) materiality disclosure, particularly the environmental aspects. Furthermore, this research explores the potential of self-disclosed ESG information based on eXtensible Business Reporting Language technology as an alternative source for predicting companies' sustainability and financial performance. An upward trend in environmental information disclosure was identified, suggesting a deepening corporate commitment to sustainability practices. Second, our correlation analysis indicated that E, S, and G materialities are increasingly disclosed in a unified manner rather than in isolation. Third, our analysis found limited evidence of a relationship between self-disclosed ESG materiality and corporate financial and ESG performance, which indicates that corporates' self-disclosure of ESG materiality is not yet sufficient to use as a standalone measure to evaluate and predict financial profitability and climate performance.
Keywords: C23; M41; O16; Q56; 330; XBRL; ESG materiality; ESG disclosure; fixed panel regression